2021
DOI: 10.36941/jesr-2021-0112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brain-based Learning in Developing Spatial Ability of Ninth Grade Students with Low Achievement in Mathematics

Abstract: This study aimed to investigate the impact of a brain-based learning training programme on improving the spatial abilities of a sample of ninth grade elementary school students in Karak Province, Jordan. The study approach is quasi-experimental, the research sample consisted of 60 students selected by the intentional method. After being divided into two groups, 30 students were in the control group and 30 students were in the experimental group. To achieve the objectives of the study, a training programme base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This was followed by the integration of BBL in secondary schools, which accounted for 16% of the studies. These include those by Al-Tarawneh et al (2021), Alanazi (2020) and Wijayanti et al (2021). 12% of the studies conducted on the integration of BBL in science classrooms focused on form school students (3 studies), namely those of Saleh (2012a;2012b;2012c), while only 8% of the studies were conducted on primary schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by the integration of BBL in secondary schools, which accounted for 16% of the studies. These include those by Al-Tarawneh et al (2021), Alanazi (2020) and Wijayanti et al (2021). 12% of the studies conducted on the integration of BBL in science classrooms focused on form school students (3 studies), namely those of Saleh (2012a;2012b;2012c), while only 8% of the studies were conducted on primary schools.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the use of brain-based learning in the classroom show that its use impacts students' achievement positively. Al-Tarawneh, A., Altarawneh, A. F., & Karaki, W. K. (2021), Alanazi (2020), Al-Balushi andAl-Balushi (2018), Saleh and Subramaniam (2019), Sani (2019), Wijayanti, K., Khasanah, A. F., Rizkiana, T., Mashuri, Dewi, N. R., & Budhiati, R. (2021) and Riskiningtyas and Wangid (2019) demonstrate that such learning improved students' achievement in primary and secondary school science, in subjects including the major core ones of biology, chemistry, physics, and mathematics. Few studies have not found a significant positive effect of the use of brain-based learning on students' achievement.…”
Section: Paper | 75mentioning
confidence: 99%
“…This implies that these constructs relies on brain-based theory principles for their integration in the classroom. Some of these construct include brain-based learning (Al-Tarawneh et al, 2021;Alanazi, 2020;Al-Balushi & Al-Balushi, 2018;Riskiningtyas & Wangid, 2019;Sani et al, 2019;Wijayanti, Khasanah, Rizkiana, Mashuri, Dewi & Budhiati, 2021), brain-based learning approach (Akyürek & Afacan, 2013) brain-based teaching (BBT) (Saleh, 2012a;Saleh, 2012b), brain-based teaching approach (Saleh, 2012c) and brain-based teaching methods (Saleh & Subramaniam, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of researchers have conducted investigations on the effect of BBT strategy on science students' achievement in secondary schools. While many of these studies have focussed on secondary school mathematics (Al-Tarawneh, Altarawneh & Karaki, 2021;Kartikaningtyas, Kusmayadi & Riyadi, 2018;Mastoni, Sumantri & Ibrahim, 2019;Mekarina & Ningsih, 2017;Noureen, Awan & Fatima, 2017;Priatna, 2017;Riskiningtyas & Wangid, 2019;Triana, Zubainur & Bahrun, 2019), others have focussed on finding the effect of BBT strategy on biology and chemistry secondary school students' achievement (Alanazi, 2020;Shabatat & Al-Tarawneh, 2016;Akyurek & Afacan, 2013;Varghese & Pandya, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%